SOCIAL APPROACH IN TAFSIR AL-QURâAN PERSPECTIVE OF HASAN HANAFI - Jamarudin, Ade (Jurnal Ushuluddin, 2015)
Hasan Hanafi states that a thorough revival in religious reforms affects social revolution and Muslimsâ politics, interpretation methodologies are needed go beyond the textual and historical interpretations, which do not take al-Qurâan in a narrow space and time in Rasulullah period, Hasan Hanafi gave a social approach in interpreting the Qurâan (almanhaj al-ijtimaâi Fi at-Tafsir). With this interpretation, according to Hanafi, an exegete who want to find the meaning of al-Qurâan do not only deduce the meaning of the text, but on the contrary, can induce the real meaning into the text. Interpret according to Hasan Hanafi means looking for something, object focus. Interpreting is to find something new among language text. It uses thematic method that is characteristic of interpretation by the scientific paradigm, which expresses the subjectivity emphasis of commitment interests and interpreter objective socially